MEMBANGUN KESEJAHTERAAN MENTAL MELALUI SYUKUR: PERSPEKTIF ISLAM DALAM PSIKOLOGI POSITIF UNTUK KEHIDUPAN YANG LEBIH BAHAGIA: Syukur dan Kesejahteraan Mental - ALI SORMIN, MUHAMMAD ALI SORMIN; Masruroh; Maulana Ibrahim (UIC (Universitas Islam Cirebon), 2024)
This article discusses the concept of gratitude from an Islamic perspective as one way to improve mental well-being in the context of positive psychology. Gratitude, as a form of appreciation for God's gifts, is believed to increase feelings of happiness and life satisfaction. In positive psychology, gratitude is recognized as one of the elements that can influence an individual's mental health and happiness. This study focuses on the relationship between the practice of gratitude in everyday life and improved mental well-being according to Islamic teachings. This approach is expected to contribute to a deeper understanding of the role of religion in improving happiness through the principles of gratitude taught in Islam.